How electromagnetic fields can influence adult stem cells: positive and negative impacts - Maziarz, Aleksandra; Kocan, Beata; Bester, Mariusz; Budzik, Sylwia; Cholewa, Marian; Ochiya, Takahiro; Banas, Agnieszka (Stem Cell Research & Therapy, 2016)
The electromagnetic field (EMF) has a great impact on our body. It has been successfully used in physiotherapy for the treatment of bone disorders and osteoarthritis, as well as for cartilage regeneration or pain reduction. Recently, EMFs have also been applied in in vitro experiments on cell/stem cell cultures. Stem cells reside in almost all tissues within the human body, where they exhibit various potential. These cells are of great importance because they control homeostasis, regeneration, and healing. Nevertheless, stem cells when become cancer stem cells, may influence the pathological condition. In this article we review the current knowledge on the effects of EMFs on human adult stem cell biology, such as proliferation, the cell cycle, or differentiation. We present the characteristics of the EMFs used in miscellaneous assays. Most research has so far been performed during osteogenic and chondrogenic differentiation of mesenchymal stem cells. It has been demonstrated that the effects of EMF stimulation depend on the intensity and frequency of the EMF and the time of exposure to it. However, other factors may affect these processes, such as growth factors, reactive oxygen species, and so forth. Exploration of this research area may enhance the development of EMFbased technologies used in medical applications and thereby improve stem cell-based therapy and tissue engineering.
Keywords: EMF (electromagnetic field); adult stem cells; cancerogenesis; regeneration; differentiation